Prospects of tourism business development in Ukraine - Popova, Tetiana; Попова, Тетяна Вікторівна; Попова, Татьяна Викторовна; Krasnodied, Tetiana; Краснодєд, Тетяна Леонідівна; Краснодед, Татьяна Леонидовна (My University, 2021)
The improvement of Ukraine’s prospects on the global tourism market is thereby caused by three components in the domestic tourism market. The first factor is an objective demand of the consumer for qualitative travel services. The second factor is an objective need for a tour operator to be competitive and create an integrated and creative tourist product with value-based pricing. The third component is the recommended use of the state aid for the development of qualitative Ukrainian tourism.
Keywords: tourism business; global market; Ukrainian tourism; value-based